Evaluating students readiness, expectancy, acceptance and effectiveness of augmented reality based construction technology education (International Journal of Built Environment and Sustainability, 2019)
Augmented reality (AR) has the potential to enhance the teaching and learning experience in construction technology which involves the learning of construction processes and understanding the construction elements. Augmented reality also provides the ability to change and improve the nature of education. This is due to the possibility of overlaying media onto the real world for content consumption using smartphones and tablets devices, which enables students to access information at anywhere and anytime. However, before implementing a new approach to teaching, the state of whether the students are ready to use AR have to be identified. This also goes toward what the students expect when using AR in learning, how do they accept using AR and effectiveness of using AR in learning. Therefore the purpose of this study is to (1) Identify the readiness of students on using AR in teaching; (2) Identifying what do the students expect when using AR in learning construction technology; (3) Identifying the student’s acceptance of AR in learning; (4) The effectiveness of AR in construction technology learning. A quantitative method of analysis has been implemented measuring the mean score of objective 1-3 based on the student’s responses to the questionnaire. On the other hand, the second phase of the study which is to determine whether using AR is effective in learning was done by comparing pre-test and post-test results. Results from the study shows assuring indicators that students accept the usage of AR in construction technology education, the application also fulfils their expectations on what AR could aid in the learning process and for student’s acceptance, the result shows that students accepted the usage of AR as a learning tool. Meanwhile, the results regarding AR effectiveness on construction technology displayed noticeable improvements regarding student’s pre-test and post-test results with 68% of students display improvements in their scores.
Keywords: Augmented Reality; Quantity Surveying; Education; Construction Technology